KASTA DAN PARIWISATA: DUA PERSOALAN DI BALIK PESONA BALI - Sunu Wasono (Faculty of Humanities, Jember University, 2011)
This article analyzes Gde Aryantha Soethama’s some selected short stories in his anthology entitled Mandi Api, published by Kompas publisher in 2006. The analysis focuses on two main problems, caste and tourism. In Balinese context, caste as local cultural form arises some sociocultural problems among Balinese, such as a cross-caste marriage. In tourism aspect, the rapid growth of tourism in Bali, in one side, give welfare for the people, but in other side arises some complicated problems especially in cultural and natural commercialization. Those two problems appear many times in the anthology showing them as the dominan problems in Balinese society. Further, for the creative writers such as Aryantha and other writers, the two problems become a kind of obsession to narrate in their creative works. Keywords: culture, caste, commercialization, tourism